SERENITY BY THE BEACH RESTORATIVE RESORT AT TANJUNG LESUNG, BANTEN - IRENE FELICIA (NIM : 15214016), CALLISTA
Nowadays, city rhymes with fast and intense life. This experience develop worker to be bored and in some interval needs time and place to rest. This place better can provide a new experience to rest that can momentarily allow people to forget the busy life in the daily work life. This is project of a restorative resort,located in Tanjung Lesung, Banten. This project intended to provide a place to rest and self‐restore for busy city workers from Indonesia and overseas. Other goal is to respond to the President decree to ensure development in Tanjung Lesung as a tourism destination in Indonesia. This project located on ten hectare alongside Lada Bay, Banten in a relative flat land contour. Resort consists ofthree types of room type with total thirty-Ã‚Â‐five units. The room types are Pool Villas, Beach Villas, and Presidentian Suites. Overall, the resort can accommodate up to seventy-Ã‚Â‐six guests. Main issues in this project area mood, comfort, privacy and restorative. The main concept, Ã‚Â“SerenitBy The BeachÃ‚Â” responded with resort zoning, circulation and presented restorative environment. Zoning is important to definitely gives maximal view and to gives privacy to each of the villas so our guests can feel the serenity. This makes nature becomes the main point of he reort as the view provider and function as a restorative tool.